A comparative cross sectional study on relationship between thyroid profile and anthropometric measurements - Bhat, Raghavendra; Katta Subraya, Prakash Rao; C., Ramachandra Bhat (International Journal of Advances in Medicine, 2020)
Background: The prevalence of obesity is increasing globally and one of the important factors associated with obesity is thought to be thyroid dysfunction. The objective of the present study was to find the incidence of subclinical hypothyroidism in overweight and obese individuals and to assess the relationship between the TSH levels and anthropometric parameters. Methods: A cross sectional study was conducted among 100 adults attending the hospital selected by a systematic random sampling method. Standard protocols were used to assess the laboratory and anthropometric parameters. Written informed consent was taken from the subjects and institutional ethical clearance was obtained before starting the study. Results: Of the 42% males and 58% females who were studied, 24% of the subjects had a BMI more than 24.99. 6% and 2% of the study subjects were having subclinical hypothyroidism and hypothyroidism respectively. There was a significant association between hypothyroidism and increased BMI values, waist circumference and waist hip ratio. Conclusions: A highly significant association was found between the serum TSH levels and the Body Mass Index, Waist circumference and Waist Hip ratio. The mean TSH levels were higher in the obese when compared to normal subjects.